1984
DOI: 10.1093/rheumatology/23.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine-Binding Prealbumin—an Index of Disease Activity or Nutritional Status in Rheumatoid Arthritis?

Abstract: Thyroxine-binding prealbumin (TBPA) concentrations were measured in 54 patients with rheumatoid arthritis (RA) and 50 control subjects. TBPA levels were significantly depressed in the RA patients, of whom 15 had values below the laboratory reference range. Although significant negative correlations were seen between TBPA and the erythrocyte sedimentation rate, C-reactive protein and alpha 1-antichymotrypsin measurements, TBPA levels showed little relationship to disease activity as assessed clinically. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Helliwell et al showed in 1984, that transerythrin was significantly decreased in the 54 RA patients with little relationship to disease activity as assessed clinically. RA patients with reduced transerythrin had an increased frequency of associated anthropometric and serum visceral protein abnormalities indicating nutritional impairment (Helliwell, Coombes et al 1984). Interestingly, increased serum levels of the negative APP leucin rich-α2-glycoprotein were identified by proteomic analysis of 326 proteins in RA patients prior to therapy.…”
Section: Apps During Ra Disease Stagesmentioning
confidence: 99%
“…Helliwell et al showed in 1984, that transerythrin was significantly decreased in the 54 RA patients with little relationship to disease activity as assessed clinically. RA patients with reduced transerythrin had an increased frequency of associated anthropometric and serum visceral protein abnormalities indicating nutritional impairment (Helliwell, Coombes et al 1984). Interestingly, increased serum levels of the negative APP leucin rich-α2-glycoprotein were identified by proteomic analysis of 326 proteins in RA patients prior to therapy.…”
Section: Apps During Ra Disease Stagesmentioning
confidence: 99%